Happiness reconstruction through Islamic guidelines in blinds in The Muslim Blinds of Indonesia (ITMI) Central Java - Izza Himawanti; Ahmad Hidayatullah; Andhi Setiyono (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2020)
Blind experience various psychological conditions that need attention, such as feeling inferior, hopeless, and useless so that it affects the level of happiness. The main purpose of this study is to determine the process of reconstruction of happiness in blind people through Islamic guidance. This research uses a qualitative method with a phenomenological approach; the process of data analysis uses the Interpretative Phenomenological Analysis technique. The subjects of the study were the blind who were members of ITMI (Indonesian Moslem Blind Association) and actively in Islamic guidance. The process of selecting subjects uses a purposive sampling method. The results showed that Islamic guidance had a positive influence in the process of reconstructing the happiness of the blind. Various processes of cognition and affection can be explored well during the process of Islamic guidance. The process of reconstructing happiness in the blind people goes through six stages, beginning with the stage of negative emotional conditions such as despair and anxiety, feeling isolated from the social environment, and then undertaking the process of finding meaning in life and reconstructing happiness. Individu dengan tunanetra seringkali mengalami berbagai kondisi psikologis yang perlu mendapat perhatian, seperti merasa rendah diri, merasa putus asa, merasa tidak berguna sehingga berpengaruh pada tingkat kebahagiaannya. Tujuan utama dari penelitian ini adalah untuk mengetahui proses rekonstruksi kebahagiaan pada penyandang tunanetra melalui bimbingan islami. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologis, proses analisis data menggunakan teknik Interpretative Phenomenological Analysis. Subjek penelitian adalah tunanetra yang tergabung sebagai anggota ITMI (Ikatan Tunanetra Muslim Indonesia) dan aktif mengikuti bimbingan islami. Proses pemilihan subjek menggunakan metode purposive sampling. Hasil penelitian menunjukan bahwa bimbingan islami memberikan pengaruh yang positif dalam proses rekonstruksi kebahagiaan individu dengan tunanetra. Berbagai proses kognisi dan afeksi dapat tereksplorasi dengan baik selama proses bimbingan Islami. Proses rekonstruksi kebahagiaan pada tunanetra melalui enam tahapan, berawal dari tahap kondisi emosi yang negatif seperti putus asa dan kecemasan, perasaan terisolasi dari lingkungan sosial, hingga kemudian melakukan proses penemuan makna hidup dan merekonstruksi kembali kebahagiaanya.